Knowledge systematization about the characteristics of existing technological means for assisting people with visual impairments - Serdechnyi, Vitalii; Barkovska, Olesia; Kovalenko, Andriy; Martovytskyi, Vitalii; Havrashenko, Anton (Національний технічний університет "Харківський політехнічний інститут", 2025)
The work is devoted to a detailed review of the main aspects of physical vulnerability for people with visual impairments, as well as technological means for navigation and adaptation to the surrounding environment, which can significantly enhance their sense of safety and security. The relevance of the topic is justified by its large social focus, because such systems help people with visual impairments to socialize more easily and ensure greater inclusion. This is particularly important in urban environments where insufficient attention is paid to inclusivity and the comfort of visually impaired individuals (e.g., lack of audible traffic lights, tactile paving, etc.). The subject of the article is the study of hardware components that ensure the functionality of support systems for people with visual impairments. The goal of this paper is to systematize knowledge about existing technological tools for people with visual impairments and to analyze the hardware characteristics of the components of such solutions.

Робота присвячена детальному огляду основних аспектів фізичної незахищеності для людей із порушеннями зору, а також технологічним засобам для навігації та адаптації людини до навколишнього середовища, які можуть значно підвищити відчуття безпеки та захищеність людини. Актуальність теми обґрунтовується великою соціальною направленістю, бо подібні системи допомагають людям із вадами зору легше проходити соціалізацію, забезпечувати більшу інклюзію, що є вкрай актуальним у містах, де приділяється мало уваги інклюзивності та комфорту незрячих людей (відсутні озвучені світлофори, тактильна плитка тощо). Предметом є вивчення апаратних компонентів, що забезпечують функціонування систем підтримки для людей з вадами зору. Метою статті є систематизація знань про існуючі технологічні засоби для людей із порушеннями зору, а також проаналізувати апаратні характеристики складових елементів подібних рішень.
Систематизація знань про характеристики існуючих технологічних засобів для супроводу людей із порушеннями зору
Keywords: technological means; accompanying people; visual impairment; assistance; microphones; dynamic objects; cameras; технологічні засоби; супровід людей; порушення зору; асистування; камери; мікрофони; динамічні об'єкти